2020
DOI: 10.2147/clep.s265619
|View full text |Cite
|
Sign up to set email alerts
|

<p>Validity of Acute Cardiovascular Outcome Diagnoses Recorded in European Electronic Health Records: A Systematic Review</p>

Abstract: Background: Electronic health records are widely used in cardiovascular disease research. We appraised the validity of stroke, acute coronary syndrome and heart failure diagnoses in studies conducted using European electronic health records. Methods: Using a prespecified strategy, we systematically searched seven databases from dates of inception to April 2019. Two reviewers independently completed study selection, followed by partial parallel data extraction and risk of bias assessment. Sensitivity, specifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 112 publications
(785 reference statements)
4
24
0
Order By: Relevance
“…Results from previous studies and systematic reviews indicate PPV and sensitivity ranging from less than 50% to over 90%. 5 , 10 , 14–17 In line with our study, most studies found that the PPV was higher than the sensitivity. Of particular interest, a previous study validating MI diagnoses in the same two registers as our study (The Norwegian Myocardial Infarction Register and the Norwegian Patient Register) found similar results as we did, with a sensitivity of 85–86% and a PPV of 95–97%.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Results from previous studies and systematic reviews indicate PPV and sensitivity ranging from less than 50% to over 90%. 5 , 10 , 14–17 In line with our study, most studies found that the PPV was higher than the sensitivity. Of particular interest, a previous study validating MI diagnoses in the same two registers as our study (The Norwegian Myocardial Infarction Register and the Norwegian Patient Register) found similar results as we did, with a sensitivity of 85–86% and a PPV of 95–97%.…”
Section: Discussionsupporting
confidence: 92%
“…Ascertaining cases through expert review of medical records is considered the gold standard of data collection methods and is widely used in health register validation studies. 5 Consequently, it is to be expected that the Tromsø Study Cardiovascular Disease Register is highly correct and complete. However, manual data collection is quite resource intensive as it involves a meticulous and time-consuming effort by trained reviewers.…”
Section: Introductionmentioning
confidence: 99%
“…For our main analysis, we used a broad definition for acute cardiovascular events of acute coronary syndrome (myocardial infarction and unstable angina), left ventricular heart failure, stroke or transient ischaemic attack, acute limb ischaemia, or cardiovascular death. We included diagnoses recorded in the CPRD or HES APC, with the codes used informed by previous studies, 21 and cardiovascular deaths (ICD-10 codes I00–I99) recorded by the ONS. In further analyses, we also assessed each cardiovascular condition separately.…”
Section: Methodsmentioning
confidence: 99%
“…The validity of electronic health record data might be high for some conditions such as stroke and acute coronary syndrome and low for others such as acute respiratory distress syndrome. 95 , 96 Furthermore, depending on the informatic tool used, data might not be available in real time, raising concerns about safety monitoring and adverse event reporting.…”
Section: Unresolved Questions For Pragmatic Trialsmentioning
confidence: 99%